Geometries, Electronic Structures and Electronic Absorption Spectra of Silicon Dichloride Substituted Phthalocyanine for Dye Sensitized Solar Cells - M. Geetha, R. Govindan, S. Manimegalai and K. Velmurugan, P. M. Anbarasan*, P. Senthil Kumar (Recent Research in Science and Technology, 2010)
The geometries, electronic structures, polarizabilities, and hyperpolarizabilities of Silicon dichloride substituted phthalocyanine dye sensitizer were studied based on Density Functional Theory (DFT) using the hybrid functional B3LYP. Ultraviolet-Visible (UV-Vis) spectrum was investigated by using a hybrid method which combines the single-excitation configuration interactions (CIS) with DFT, i.e. CIS-DFT(B3LYP). Features of the electronic absorption spectrum in the visible and near-UV regions were assigned based on CIS-DFT calculations. The absorption bands are assigned to nâ†’Ï€* transitions. Calculated results suggest that the three lowest energy excited states of Silicon dichloride substituted phthalocyanine are due to photoinduced electron transfer processes. The interfacial electron transfer between semiconductor TiO2 electrode and dye sensitizer is due to an electron injection process from excited dye to the semiconductorâ€™s conduction band. The role of Silicon dichloride in phthalocyanine geometries, electronic structures and electronic absorption spectra were analysed and these results were concluded that Silicon dichloride substituted phthalocyanine used in Dye Sensitized Solar Cells (DSSC) give a good conversion efficiency.